Lazer, ninho vazio e terceira idade: estudo sobre administradores de empresas na cidade de São Paulo - Giglio, Karin Maria Ribas Haikal (2006)
There is little research concerning cultural and entertainment activities practiced by elderly people, since it is still believed by many that retirement or old age signify that retirees and elderly people always stay at home and never go out. The purpose of this paper is to question this paradigm and to demonstrate that elderly citizens who belong to classes A and B are potential consumers for the cultural and entertainment industry, in which age is not a restrictive factor. Upon the consideration of demographic tendencies presented by social specialists, concerning the growth of the elderly population in relation to the general Brazilian population, in combination with the increase in life expectancy, it is possible to observe the existence of a growing segment with great consumer potential, which has not been explored by the market. This research examines the relationships between life cycle, habitus, gender, civil status and profession, and leisure practices, especially focusing on leisure activities practiced in and outside the house by people who have entered old age; this research also seeks to understand the significance of such relationships. The population for this exploratory research consisted of former undergraduate students of Business Administration at Getúlio Vargas Foundation, and was implemented by means of interviews following a script. The findings revealed that this segment of the population consists of people who are potential tourists, who love to go to the movies and eat out, and who enjoy going to concerts, museums, and art exhibits. They enjoy and practice sports and watch television regularly. In addition they enjoy electronic media, love reading books, newspapers and magazines, and appreciate good music. Usually family members participate in such activities which includes a social and family aspect to most of these activities. The results obtained reveal the need for a new market vision in which the needs, restrictions and behavior of elderly consumers are considered.